P034 Presence of a specific defect in M2 polarization of blood monocytes from patients with rheumatoid arthritis, associated with increased microRNA-155. (March 2019) - Paoletti, A; Rohmer, J; Ly, B; Pascaud, J; Riviere, E; Nocturne, G; Mariette, X
Abstract : Career situation of first and presenting author: Post-doctoral fellow. Introduction: Macrophages contribute in situ to the rheumatoid arthritis (RA) pathogenesis. Two distinct states of polarization have been recognized: the 'classically activated' (M1) and the 'alternatively activated' (M2). miRNAs are a recently discovered class of post-transcriptional regulators. Of particular relevance in RA is miR155. Its expression is upregulated in RA synovial monocytes, macrophages and fibroblasts.bIts overexpression in macrophages is associated to the production of pro-inflammatory mediators. Objectives: Here, we assessed monocytes capacity of differentiation into M2 and implication of miR155 in RA patients or controls (HD, CTD or SpA). Methods: Purified monocytes were incubated 6 day in the presence human serum AB (SAB) (M2). Expressions of total macrophages markers (CD11b-CD71 ), M2 markers (CD163, CD206, IL-10 and Arginase ) and M1 markers (INOS, IFR5 and IL1β ) were evaluated by flow cytometry, ELISA or immunofluorescence. The microRNA transfections were performed using AMAXA technology . Results: We observed a significant decrease of macrophages induction only by SAB in RA patients as shown by a decreased expression of CD11b-CD71 . We have found a specific decreased level of M2 markers. Moreover, we found ex vivo and in vitro that Adalimumab but not Etanercept or non-anti-TNF drugs were able to partially correct this defect of M2 We confirmed that under SAB treatment, RA monocytes have a propensity for preferential maturation towards a pro-inflammatory M1-like phenotype instead of M2, thus contributing to synovial inflammation. We have hypothesized the involvement of miR155 on this defect. Indeed, miR155 is induced in monocyte or macrophages and drives their inflammatory response by epigenetic regulation that lead to M1 polarization. miR155 is increased in monocytes and M2 RA compared to controls. Subsequently we transfected monocytes from HD with miR155 mimic and we observed a decrease differentiation in M2. Conversely preliminary experiments on RA monocytes transfection with a miR-155 inhibitor allowed the restoration of M2 polarization. Conclusions: RA patients have a specific impaired maturation of monocytes to M2 as much in phenotype and in function while the differentiation to the M1 phenotype is maintained. The use of monoclonal anti-TNF restores M2 polarization defect while Etanercept or non anti-TNF drugs do not restore M2. This lack of M2 polarization is associated with miR155 increase in RA patients that leads to IFR5/INOS expression. Preliminary experiments showed that transfection of RA monocytes with an antagomiR155 may correct this lack of M2, justifying the proof of concept trial of monocytes-targeted nanoparticles containing microRNA in CIA mouse models. Disclosure of Interest: None declared.